Reference values for circulating pregnancy‐associated microRNAs in maternal plasma and their clinical usefulness in uncomplicated pregnancy and hypertensive disorder of pregnancy. Issue 5 (8th March 2018) - Murakami, Yuko; Miura, Kiyonori; Sato, Shuntaro; Higashijima, Ai; Hasegawa, Yuri; Miura, Shoko; Yoshiura, Koh‐ichiro; Masuzaki, Hideaki
Abstract: Aim: The aim of this study was to establish the reference values for circulating pregnancy‐associated placental microRNAs in maternal plasma and clarify their clinical significance in patients with hypertensive disorder of pregnancy (HDP). Methods: Blood samples were collected from 145 women with uncomplicated pregnancies (24, 26, 31 and 32 women at 12, 23, 30 and 36 weeks of gestation, respectively, and 32 women 1 day after delivery). Plasma concentrations of pregnancy‐associated placental microRNAs (miR‐515‐3p, miR‐517a, miR‐517c and miR‐518b) were measured by quantitative real‐time reverse‐transcription polymerase chain reaction. Reference values for each microRNA were determined by the line of best fit and 95% prediction interval and are expressed as logarithmic transformation. To clarify the clinical significance of these reference values, we measured the plasma concentrations of pregnancy‐associated microRNAs in a different population comprising 33 pregnant women with HDP and 44 women with uncomplicated pregnancies. Results: Reference values for circulating pregnancy‐associated placental microRNAs on chromosome 19 miRNA clusters showed an increasing tendency as pregnancy progressed and decreased significantly 1 day after delivery ( P < 0.05). The sensitivity and specificity of each reference value were 57.6% and 93.2% for miR‐515‐3p, 63.6% and 75.0% for miR‐517a, 75.8% and 79.5% for miR‐517c and 63.6% and 75.0% for miR‐518b, respectively. The positive and negative predictive values of each reference value were 86.4% and 74.5% for miR‐515‐3p, 65.6% and 73.3% for miR‐517a, 73.5% and 81.4% for miR‐517c and 65.6% and 73.3% for miR‐518b, respectively. Conclusion: Establishing the reference values for circulating pregnancy‐associated placental microRNAs in maternal plasma could be useful for the evaluation of HDP.